Produção de sentidos e de significados de estudantes do ensino médio sobre o conceito de volume e capacidade de prismas - Magalhães, Marcos Hirota (Universidade Federal de São Carlos, 2014)
The objective of this research is to analyze the production of feelings and meanings that high-school students experience when enrolled in activities related to the concept of the Prisma Volume. The activities were organized by the teacher and considered the contents of composition and decomposition of figures. During the development of the manipulatives activities, for example, the golden material was used. Acrylic prisms were also used so that students could manipulate and calculate their volumes. The research is qualitative and can be characterized as a Case Study. The question guiding this study is: what are the feelings and the meanings that can be produced by high-school students when they experience educational activities while studying the concept of Materials Volume? The survey was conducted in a private school in São Carlos-SP, where classes were filmed and, after the development of activities, an analysis of their speeches and writings was held based on the interactions within the classroom with the teacher s mediation. Students performed three activities in thirteen classes, which were divided didactically, to be analyzed in the form of teaching episodes. Thus, information that enabled the understanding of what is interpreted to be the production of feelings and meanings made by students were pooled. Results suggest that the production of feelings and meanings explicited by the students are related to the skill of spatial visualization of the prism and its constituent elements, such as: measurement, size, composition area and perimeter.
Keywords: Geometria; Prismas; Atividade orientadora de ensino; Teaching geometry; Prism volume; Guiding teaching activity; CIENCIAS EXATAS E DA TERRA